2000
DOI: 10.1034/j.1399-3003.2000.16f06.x
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting life expectancy of children with cystic fibrosis

Abstract: In this study the authors aimed to produce a model for predicting the life expectancy of children with severe cystic fibrosis (CF) lung disease.The survival of 181 children with severe CF lung disease referred for transplantation assessment 1988±1998 (mean age 11.5 yrs, median survival without transplant 1.9 yrs from date of assessment) were studied. Proportional hazards modelling was used to identify assessment measurements that are of value in predicting longevity.The resultant model included low height pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 16 publications
2
62
0
4
Order By: Relevance
“…This formula had been derived from an earlier survival study of children with severe CF lung disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…This formula had been derived from an earlier survival study of children with severe CF lung disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…In field test studies, the indices most commonly used for patient evaluation are the distance walked, the lowest Sp,O 2 and fC [215]. Some authors have found that V9O 2 ,peak in patients with CF was correlated with 6-MWD, with the correlation coefficient increasing if age, weight, FVC, FEV1 and DL,CO were added to the prediction equation [216,217].…”
Section: V9o 2 Peak and Ventilatory Indicesmentioning
confidence: 99%
“…National systems can be structured so as to take into account expert clinician judgment, as was demonstrated during this meeting by descriptions of the British and Canadian systems (7,134,135). It may well be the case, as some have argued, that outcomes for transplantation in the United States are determined to a large part by bureaucratic processes rather than variations in surgical or medical procedures.…”
Section: In Spite Of Revisions In National Policies To Manage Lung Trmentioning
confidence: 99%
“…The disadvantage is that by listing children fairly late in the course of their disease, there are inevitably some who will die before receiving organs. In common with most other transplant centers, we use a variety of clinical and physiological data to prognosticate in children referred to us in an attempt to identify the correct time of listing (134,13,15). However, any such survival estimation is inexact in individuals, and occasionally children will die before even being listed.…”
Section: Paul Aurora and Helen Spencermentioning
confidence: 99%
See 1 more Smart Citation